Critical appraisal of bevacizumab in the treatment of metastatic colorectal cancer - Zoratto, Federica (Dove Medical Press, 2012)
Colorectal cancer is one of the most common cancers worldwide. The prognosis of patients with metastatic colorectal cancer in recent years has increased from 5 months with best supportive care to nearly 2 years with chemotherapy combined with bevacizumab, an antivascular endothelial growth factor monoclonal antibody. New prognostic and predictive biomarkers have been identified to guide chemotherapy in metastatic colorectal cancer, such as KRAS and BRAF oncogenes. However, the status of these oncogenes does not affect the efficacy of bevacizumab, and biomarkers predicting response to treatment with bevacizumab are still lacking. Addition of bevacizumab to regimens based on fluoropyrimidines or irinotecan has been shown to improve overall survival in treatment-naïve patients with metastatic colorectal cancer. Similarly, a significant increase in overall survival rate is achieved by adding bevacizumab to fluoropyrimidines and oxaliplatin in patients with disease progression. Bevacizumab has been found to be effective even when used as third-line therapy and later. In addition, cohort studies have shown that bevacizumab improves survival significantly despite disease progression. Finally, bevacizumab therapy in the neoadjuvant setting for the treatment of liver metastasis is well tolerated, safe, and effective.